Aplikasi koordinasi modular dalam sistem bantuan rekabentuk berkomputer - Sulaiman, Muhammad Khairi (2010)
The method and implementation of Modular Coordination design is too complicated, time consuming and not popular among architects. Thus, this thesis will do a detailed investigation of Modular Coordination design method to find out what has made this method so difficult to use. At the end of the study, this thesis will present a solution and introduces a computer aided Modular Coordination design system. The Malaysian government has promoted the application of Modular Coordination for the purpose of making the Open Building System a reality. Currently, the response towards the implementation of Modular Coordination has not been encouraging although there have been efforts by the government to ensure its success. The reason is because it must conform to MS:1064 standard and specification where space and building components have to be designed in accordance with specific positioning and dimensioning. The use of computer as a support tool has always been regarded as ubiquitous solution to solve complex design problems and therefore, has the potential to aid Modular Coordination design. The research started with literature review and initial survey to assess design facts and to identify the level of complexity in Modular Coordination design. It is followed by interviewing six architects to ascertain how the conventional design process for Modular Coordination is currently done. Consequently, after the findings and conclusion, a solution to overcome the problem is presented where a computer aided Modular Coordination design is proposed. To simulate and show how the system works, REVIT software was customised for this system. The system is later implemented for a government quarters project which was designed earlier using conventional Modular Coordination design method to identify its strength and weakness. The study found that Modular Coordination design rule is posing a lot of constraints and tends to restrict architects during the early design stage, and the use of computer does not help the architects in conforming to the rule. To overcome these problems, a computer aided Modular Coordination Design System that complies with the Modular Coordination rule is introduced which initiated the design process with parametric objects. A comparison between both design methods found that the Modular Coordination design that uses the proposed system has more advantages that includes; conforming to Modular Coordination rule at the early design stage, easier to use and takes less time to produce. The thesis has proposed a Computer Aided Modular Coordination Design System for architects to aid design implementation according to the Modular Coordination rules at ease.